Development of a Model of Asthma Management in Children Based on Beliefs by Parents in The Concept of The Health Belief Model - Wiga, Sandi Alfa (Journal of Global Research in Public Health, 2018)
Introduction: Asthma in children causes loss of school days, and also causes growth in children. Parents have a responsibility to manage asthma, they need asthma management education for children who can increase their wisdom in managing it. The research objective was to develop a model of asthma management education in children based on beliefs in the concept of the Health Belief Model. Method: quasi-experimental research with 66 respondents, probability sampling method through simple random sampling. Using 3 HBM model development questionnaires belief, threat and behavior. Statistical analysis : using a paired t-test, Mann Whitney test, linear regression adjusted for each variable studied in developing HBM. Results and Analysis : education on trust (p <0.001), confidence in threats (p = 0.001), threats towards behavior (p <0.001), educational influence on behavior (p <0.001). Discussion and Conclusion: Parents' beliefs about their ability to discuss existing problems are very important to overcome recurrence. Increased confidence in skills, increased satisfaction and self-confidence, with an effective increase in good conditions by children with asthma.